2016
DOI: 10.4081/ijfs.2016.5691
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the freezing point of buffalo milk

Abstract: The aim of this study was to evaluate the basic freezing point of buffalo milk. Bulk milk samples were collected from buffalo and cattle farms in Caserta area from 2008 to 2014. The analysis involved a total of 1886 buffalo milk samples and 1711 bovine milk samples. These were also tested for fat, protein and lactose contents by means of infrared spectrometry. The freezing point was determined by means of a thermistor cryoscope. Data underwent statistical analysis. Our research showed an average freezing point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 5 publications
1
7
3
1
Order By: Relevance
“…The FP mean value here reported is lower than values reported by Pesce et al (2016) who evidenced a mean value of - 0.536°C in bulk tank buffalo milk collected in Campania region (Italy) and higher than values reported by Hofi et al , (1966) who evidenced a FP ranging from -0.552 to - 0.558°C. Differently, our results are very close to the results reported by Kedzierska- Matysek et al (2011) who found a mean FP value of -0.544°C in Jersey milk, a cow breed having a milk protein and lactose content similar to buffalo milk.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…The FP mean value here reported is lower than values reported by Pesce et al (2016) who evidenced a mean value of - 0.536°C in bulk tank buffalo milk collected in Campania region (Italy) and higher than values reported by Hofi et al , (1966) who evidenced a FP ranging from -0.552 to - 0.558°C. Differently, our results are very close to the results reported by Kedzierska- Matysek et al (2011) who found a mean FP value of -0.544°C in Jersey milk, a cow breed having a milk protein and lactose content similar to buffalo milk.…”
Section: Discussioncontrasting
confidence: 80%
“…Actually, data regarding the mean value of freezing point in buffalo milk are limited. In Italy, Pesce et al (2016) shown a FP mean value of -0.536 °C whereas, in India, Prajapati et al (2007) found a FP ranging between −0.584 °C and −0.532°C with a mean value of −0.558°C.…”
Section: Introductionmentioning
confidence: 99%
“…The mean fat measurements for all analyzed buffalo milk samples from the period of this study was 5.5 g/100 g, and the fat content ranged from 4.26 g/100 g to 9.57 g/100 g. The overall median for protein was calculated at 4.06 g/100 g with values ranging from 3.42 g/100 g to 4.60 g/100 g. The mean fat and protein contents were lower than those reported in studies conducted in Italy (Pesce et al ., 2016; Pasquini et al ., 2018) and the USA (Han et al ., 2012), while they were similar to studies performed in Egypt (Elshaghabee et al ., 2017) or other parts of Brazil (Filho et al ., 2014; Bailone et al ., 2017; Sales et al ., 2018). Total solids were measured at an average value of 15.5 g/100 g, ranging from 13.56 g/100 g to 19.53 g/100 g. This average was very close to other studies conducted in Brazil (Filho et al ., 2014; Bailone et al ., 2017; Sales et al ., 2018), but lower than those reported by Han et al .…”
Section: Resultsmentioning
confidence: 99%
“…The FP of milk is related to its soluble constituents and is usually used to detect water added to milk. It has been reported that the basic FP of buffalo milk is lower than cow's milk (Pesce et al ., 2016) and can be affected by seasonality and farm size (El-Salam and El-Shibiny, 2011). The average result for FP was −0.527°C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation